Bony canals along the course of middle meningeal artery in dry skulls - Bindu Aggarwal; Madhur Gupta; Harsh Kumar (Wolters Kluwer Medknow Publications, 2012)
Background: The middle meningeal artery courses in the middle cranial fossa and divides into two or three branches. The branches of the artery are sometimes enclosed within a bony canal. The artery and its branches are likely to get torn in cases of epidural hematomas and may require ligation. Aims: The aim of the study is to report the variations in the branching pattern of middle meningeal artery and incidence of bony canals along the course of these branches. Materials: The study material consisted of 77 bases of dry skulls (154 sides) and the findings were supplemented with dissection of four cadaveric skulls. Results and Conclusions: The length of stem of middle meningeal artery, from foramen spinosum to its division into branches varied from 0.56 to 5.83 mm on the right side and 0.58- 7.53mm on the left. The mean length of the stem was 3.04 on the right side and 3.01 on the left (S D ± 1.4). The middle meningeal artery divided into anterior and posterior branches in all the sides of skull. A middle branch constituting a third branch of middle meningeal artery was observed in 44.15% (68 sides) which arose either from its anterior 35.29% (24 sides) or posterior branch 64.71% (44 sides). Bony canals were observed in 39.61% (61 sides). The anterior branch was enclosed in a bony canal in 37.66% (58 sides) and the posterior branch in 1.94% (3 sides). The variations in the course, branching pattern and bony canals along middle meningeal artery are of clinical significance while treating extradural and subdural hemorrhages as due to these variations and presence of bony canal in course of middle meningeal artery, ligation of the vessel may be totally or partially insufficient.